Early hospital discharge and readmission jaundice in term babies - Saleem, Saleena; Nair, Rekha S.; Nair, P. Madhava Chandran (International Journal of Contemporary Pediatrics, 2020)
Background: Hyperbilirubinemia is a common and often benign disease in the neonatal period. It is the most common cause of readmission in early neonatal period. Prolonged hyperbilirubinemia can result in chronic bilirubin encephalopathy. Increasing the hospital stay of otherwise healthy neonates is not an acceptable solution for medical, social and economic constraints. So, identifying the risk factors for readmission assumes importance. Aim of our study is to identify the risk factors for readmission jaundice in our hospital. Methods: In this study, authors used a questionnaire to find out the risk factors for readmission in those babies who were readmitted with jaundice within 3 weeks of life to our hospital. During the study period, routine treatment practices were followed and there was no deviation from the standard of care for the purpose of research. Results: Of the 2297 deliveries during this study period, 93 babies (4%) were readmitted with jaundice. Among the 93 babies, prevalence of blood group incompatibility was one of the common causes of neonatal jaundice. 46.2% of the babies had an early discharge. Total Serum bilirubin levels were measured by a hospital-based bilirubin assay. Babies with serum bilirubin level above photozones as per American Academy of Pediatrics practice guidelines 2004 were identified and subjected to photo therapy. All the babies in this study responded to photo therapy. No other interventions were needed. Conclusions: Though an early discharge is the most cost-effective strategy in this era of high medical expenditure, we can identify certain high-risk babies, prone for readmission. Blood group incompatibility, infants of primiparous mothers and GDM mothers are more prone to readmission jaundice. Identifying these high-risk babies and educating the mothers is a more cost-effective strategy than prolonging the hospital stay for all babies.